2019
DOI: 10.2147/dddt.s188760
|View full text |Cite
|
Sign up to set email alerts
|

<p>Preclinical pharmacodynamic and pharmacokinetic characterization of the major metabolites of cariprazine</p>

Abstract: Introduction: Cariprazine, a dopamine D3-preferring D3/D2 receptor partial agonist and serotonin 5-HT1A receptor partial agonist, has two major human metabolites, desmethyl-cariprazine (DCAR) and didesmethyl-cariprazine (DDCAR). The metabolite pharmacology was profiled to understand the contribution to cariprazine efficacy.MethodsIn vitro receptor binding and functional assays, electrophysiology, animal models, microdialysis, and kinetic-metabolism approaches were used to characterize the pharmacology of DCAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Some compounds can increase basal DA release in the prefrontal cortex and striatum such as the D3R preferring D2/D3 antagonist IRL-790 also known as mesodopetam [ 244 ]. The D3R preferring partial agonist cariprazine increases DA release in the nucleus accumbens and ventral hippocampus [ 245 ] as well as DA turnover in the striatum [ 204 ] in intact animals. Cariprazine also increases DA release in the prefrontal cortex in a PCP-exposure model of acute psychosis [ 246 ].…”
Section: Site and Mechanism Of Action For D3r Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some compounds can increase basal DA release in the prefrontal cortex and striatum such as the D3R preferring D2/D3 antagonist IRL-790 also known as mesodopetam [ 244 ]. The D3R preferring partial agonist cariprazine increases DA release in the nucleus accumbens and ventral hippocampus [ 245 ] as well as DA turnover in the striatum [ 204 ] in intact animals. Cariprazine also increases DA release in the prefrontal cortex in a PCP-exposure model of acute psychosis [ 246 ].…”
Section: Site and Mechanism Of Action For D3r Antagonistsmentioning
confidence: 99%
“…A study by Millan et al (2010) [201] shows that the D3R preferring antagonist S33138 improves cognitive performance in Rhesus monkeys. Not only full antagonists (agents without intrinsic activity), but also compounds that are D3R preferring partial agonists (functioning as antagonists under high dopaminergic tone) such as BP-897, cariprazine, or its metabolite, didesmethyl-cariprazine also improve cognitive deficits in various animal models [150,194,[204][205][206] (Table 4). In case of cariprazine this pro-cognitive action translates well into humans, as it improved cognition in schizophrenic patients, which is not typical to antipsychotics [207].…”
Section: Role In Learning and Cognitionmentioning
confidence: 99%
“…10 What this means is that the actions of DDCAR, which has the same, if not more potent, actions on neurotransmitter receptor binding, is responsible for efficacy and tolerability. 22 Thus, on the one hand, effective cariprazine dose may rise over several weeks even though daily dosing stays the same; on the other hand, missing a dose may not be a devastating event. In fact, cariprazine is the only antipsychotic with recommended every-other-day dosing (when cariprazine is taken in the presence of a strong CYP3A4 inhibitor).…”
Section: Cariprazine Mechanism Of Actionmentioning
confidence: 99%
“…In this study, the EEG modulatory effect of cariprazine was most prominent at the 0.3 mg/kg dose, which is in accordance with the pharmacologically active dose range described in the paper by Gyertyán et al (2011) for behavioural endpoints. Furthermore, occupancy findings for cariprazine, described in a recent paper (Kiss et al, 2019), revealed ED 50 values of 0.23 and 0.43 mg/kg for the inhibition of striatal dopamine D 2 receptor and cerebellar dopamine D 3 receptor binding, respectively. It is therefore reasonable to assume that the effects of cariprazine on the sleep EEG could be attributed to its interactions with these dopamine receptors.…”
Section: Discussionmentioning
confidence: 88%